Expanding the Spectrum of NUBPL-Related Leukodystrophy - Tonduti, Davide; Zambon, Alberto A.; Ghezzi, Daniele; Lamantea, Eleonora; Izzo, Rossella; Parazzini, Cecilia; Baldoli, Cristina; van der Knaap, Marjo S.; Fumagalli, Francesca (Neuropediatrics, 2023)
Mitochondrial leukodystrophies constitute a group of different conditions presenting with a wide range of clinical presentation but with some shared neuroradiological features. Genetic defects in NUBPL have been recognized as cause of a pediatric onset mitochondrial leukodystrophy characterized by onset at the end of the first year of life with motor delay or regression and cerebellar signs, followed by progressive spasticity. Early magnetic resonance imagings (MRIs) show white matter abnormalities with predominant involvement of frontoparietal regions and corpus callosum. A striking cerebellar involvement is usually observed. Later MRIs show spontaneous improvement of white matter abnormalities but worsening of the cerebellar involvement evolving to global atrophy and progressive involvement of brainstem. After the 7 cases initially described, 11 more subjects were reported. Some of them were similar to patients from the original series while few others broadened the phenotypic spectrum. We performed a literature review and report on a new patient who further expand the spectrum of NUBPL-related leukodystrophy. With our study we confirm that the association of cerebral white matter and cerebellar cortex abnormalities is a feature commonly observed in early stages of the disease but beside the original and so far prevalent presentation, there are also uncommon phenotypes: clinical onset can be earlier and more severe than previously thought and signs of extraneurological involvement can be observed. Brain white matter can be diffusely abnormal without anteroposterior gradient, can progressively worsen, and cystic degeneration can be present. Thalami can be involved. Basal ganglia can also become involved during disease evolution.
Keywords: leukodystrophy; NUBPL; complex I; mitochondrial